PEMBELAJARAN METODE YANBU’A DALAM KEMAMPUAN MEMBACA HURUF HIJAIYAH PADA ANAK USIA DINI DI TPQ BENDUNGAN - Muhammad Saefullah; Siti Lailiyah; Dina Rosyana (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
The Yanbu’a method of learning is very common in the Al-Qur'an Education Park, to be precise at the TPQ of this dam. The main problem that is often faced by children is the lack of fluency in reading hijaiyah letters. Because not every child is fully able to read fluently, sometimes some are still taught how to read without walking on their own. The purpose of the research here is to find out the learning of the Yanbu’a method in the ability to read hijaiyah letters in early childhood at TPQ Bendungan. The steps for learning the Yanbu’a method are reading a prayer to start learning, reading asmaul husna, reading sholawat kalamun qodimun, and al-fatihah. This research is a class action research (CAR) that is qualitative in nature, by taking locations at the Dam TPQ. Data collection by means of interviews, observation and documentation. The results of the research from learning the Yanbu’a method are that some children are still not fluent in reading hijaiyah letters at the Dam TPQ. Therefore, the Yanbu’a method is very important to do every day. In order to facilitate children's reading on hijaiyah letters.